Lateral costal artery as a culprit for the steal phenomenon after coronary artery bypass grafting: a case report and review of the literature - Michal Trebišovský; Marián Homola; Adrián Kolesár; Štefan Lukačin; Anton Bereš (Journal of Cardiothoracic Surgery)
Abstract Background The left internal thoracic artery (LITA) has been widely accepted as the standard for revascularizing the left anterior descending artery during coronary artery bypass grafting (CABG) surgery. However, in 10–20% of cases, the LITA may lead to unsecured side branches to the chest wall, particularly the lateral costal artery (LCA), potentially resulting in postoperative chest angina. Case presentation We report the case of a 58-year-old patient who experienced persistent angina eight months after having undergone coronary artery bypass grafting (CABG) due to the steal phenomenon caused by a thick lateral costal artery (LCA). The LCA was found to be 2/3 the diameter of the left internal thoracic artery (LITA) with the decision to obliterate the LCA. Following LCA obliteration, the patient’s exertional angina was resolved. Conclusions LCA may pose a potential issue in terms of coronary steal after CABG. Understanding the anatomy of the LITA with LCA variation and widening the opening of the pleura may be beneficial in preventing postoperative steal in selected cases.